Investigação geofísica com os métodos Slingram e GPR de contaminação salina na vila de Caratateua Curuçá-Pará - SILVA, Anderlon Andrade da (2019)
This work presents a study of the shallow subsurface to investigate possible contamination caused by salt water arising shrimp ponds. The study was conducted at the Our Lady of Fatima Caratateua located in the village, municipality of Curuçá – Para. The electromagnetic geophysical methods were used Slingram and ground penetrating radar (GPR). Collected was water from wells for laboratory measures of physical and chemical parameters, electrical conductivity, pH, TDS and salinity and depth measurements of the static level and wells. The interpretation of data Slingram identified the presence of more conductive areas (probably saline contamination) and more resistive zones (possible blocks laterites). Through the GPR data identified the presence of attenuated zones probably indicating contamination saline and reflectors that indicate the laterite blocks and the local water table. The results of the correlation between the data, shown by contours maps, 3D block-diagram, pseudo-sections and radargrass demonstrate that the combination of the two methodologies HLEM electromagnetic and GPR is well suited for this type of research.